Diagnostic Role of Serum Adenosine Deaminase In Smear-negative Pulmonary Tuberculosis - Ali, Nishat; Ali, Isha Abdullah; Azad, Khan Abul Kalam (Bangladesh Journal of Medicine, 2024)
Background: Diagnosis of tuberculosis is not always easy, particularly if it is a case of sputum smear-negative pulmonary tuberculosis (SNPTB). Patients with respiratory symptoms resembling SNPTB are difficult to differentiate based on clinical features, chest X-ray, and Xpert MTB/RIF negativity. So, additional diagnostic test with high sensitivity and specificity is needed to increase the yield of the ongoing diagnostic strategy for SNPTB. Adenosine deaminase (ADA) is now being widely used for the diagnosis of TB particularly in effusion fluids due to its simplicity, low cost, and quick available results, it is not always possible to access effusion fluids and therefore, it would be helpful to take advantage of serum levels. Therefore, the purpose of the study was to assess the role of serum ADA in the diagnosis of SNPTB. Methods: This cross-sectional analytical study was conducted in Dhaka Medical College & Hospital, Dhaka from March 2019 to September 2021. A total of 140 patients were included in this study and divided into two groups according to selection criteria: Group I (SNPTB, n=62), and Group II (non-TB pulmonary diseases, n=78). ADA estimation was carried out using the sensitive colorimetric method described by Guisti and Galanti with a BIOSIC kit. After the collection of all the required data, analysis was done by SPSS 24.0. Results: The mean age of the study patients was 48.02 ± 9.60 years (23-73 years) with male predominance in both Group I and Group II (71 % and 60.3%, respectively, p>0.05). Non-TB pulmonary cases were significantly older than SNPTBpatients (52 ± 8.56 vs 43.02 ± 8.49 years, p<0.001). SNPTB patients had a significantly higher frequency of cough, fever, and weight loss compared to non-TB pulmonary cases (p<0.05). In contrast, chest pain and shortness of breath were more frequent in Group II than in Group I (p<0.05). Serum ADA was significantly higher among SNPTB patients compared to non-TB pulmonary cases (48.16 ± 12.13 vs 18.64 ± 7.85 IU/L, p<0.001). ROC analysis of serum ADA in the diagnosis of patients with SNPTB found an AUC of 0.9850 (95% CI, 0.969-1.00) which was statistically significant (p<0.001). A cut-off value of serum ADAe”33 IU/L showed sensitivity, specificity, NPV, PPV, and accuracy of 93.55%, 94.87%, 94.87%, 93.55%, and 94.29%, respectively to correctly diagnose SNPTB cases. Conclusion. This study finding stated that serum ADA may be a useful marker to distinguish SNPTB from non-TB respiratory diseases. However, further study with a more generalized study population is recommended. Bangladesh J Medicine 2024; 35: 61-69